1998
DOI: 10.1002/(sici)1099-0739(199803)12:3<147::aid-aoc687>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SnBr4 and di‐n‐butyl tin diacetate as laser‐assisted chemical vapor deposition precursors for SnO2‐based gas sensors

Abstract: Laser-assisted chemical vapor deposition (LCVD) was utilized to produce SnO 2 films from SnBr 4 plus air, O 2 or N 2 O. SnO 2 films were successfully generated using either 222 or 308 nm laser pulses but there was evidence for film contamination when using less than 60 mJ/ pulse laser energies at 222 nm. Films were characterized using ultraviolet absorption spectroscopy; the spectra of films with impurities resembled the spectrum of SnBr 4 . AFM images were obtained which indicated that this LCVD route produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Along with thermal oxidation of physical-vapor-deposited atomic tin films, other reported methods for varying the stoichiometry of tin oxide materials include use of Sn(IV) and Sn(II) precursors in organometallic chemical vapor deposition, as well as oxidation of the surface of thin films initially prepared by pulsed laser deposition . Previous work in our laboratory , has utilized laser-assisted chemical vapor deposition (LCVD) to produce SnO 2 and doped SnO 2 films. Preliminary experiments indicate that the LCVD technique can also be adapted to generate films containing polycrystalline SnO from Sn(IV) precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Along with thermal oxidation of physical-vapor-deposited atomic tin films, other reported methods for varying the stoichiometry of tin oxide materials include use of Sn(IV) and Sn(II) precursors in organometallic chemical vapor deposition, as well as oxidation of the surface of thin films initially prepared by pulsed laser deposition . Previous work in our laboratory , has utilized laser-assisted chemical vapor deposition (LCVD) to produce SnO 2 and doped SnO 2 films. Preliminary experiments indicate that the LCVD technique can also be adapted to generate films containing polycrystalline SnO from Sn(IV) precursors.…”
Section: Introductionmentioning
confidence: 99%
“…This task is very important, since the electrophysical and surface properties of polycrystalline metal oxide films as well as the parameters of devices based on these materials depend strongly on the morphology of the films, described by parameters such as the size and the shape of grains and crystallites, film texturing, surface roughness and porosity [1]. It has been found that these structural parameters of the films can be controlled by selecting an appropriate substrate, deposition temperature, properties of the precursors, doping elements, film thickness or deposition method [1][2][3][4][5][6]. However, these approaches optimizing the morphology of the film have significant limitations on the possible change in the film structure that can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organotins have been mainly used in material science to process doped or undoped tin dioxide thin films by pyrosol deposition, spray pyrolysis, and chemical vapor deposition, or to prepare under vacuum silica- or alumina-supported tin species . However, few research efforts focused on the preparation of functional materials from organotin precursors by low-temperature solution routes, for instance to obtain stable hybrid materials in which both organic and inorganic components are tightly associated through covalent bonds .…”
Section: Introductionmentioning
confidence: 99%